Oceanographic Data of the 30th Japanese Antarctic Research Expedition from November 1988 to March 1989 - イケダ, シュンイチ; マツモト, ケイゾウ; Ikeda, Syunichi; Matsumoto, Keizou (National Institute of Polar Research, 1991)
P(論文) departmental bulletin paper